2017
DOI: 10.1051/ctv/20173202102
|View full text |Cite
|
Sign up to set email alerts
|

Agronomical characterization of minority grapevine cultivars from Asturias (Spain)

Abstract: SUMMARYGrapevine (Vitis vinifera L.) was an important crop in the past in Asturias (Northwestern Spain), but the phylloxera and later the boom of the mining industry almost led to its extinction in the last century. Currently, the grape growers are rescuing the old cultivars present in the region from ancient times, but the long period of abandon has originated a lack of information about their characteristics. Four red ('Albarín Negro', 'Carrasquín', 'Verdejo Negro' and 'Mencía') and two white ('Albarín Blanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In this view, recent studies have shown that the intra-varietal diversity of commercial varieties could be exploited to maintain grape quality under future climate conditions [18,29,30]. On the other hand, in the last decade, there has been a renewed interest in recovering and studying local ancient cultivars to preserve the genetic resources of each grape-growing region [31][32][33][34]. This trend could be a valuable strategy to sustain higher genetic diversity, as well as product diversity in the markets.…”
Section: Introductionmentioning
confidence: 99%
“…In this view, recent studies have shown that the intra-varietal diversity of commercial varieties could be exploited to maintain grape quality under future climate conditions [18,29,30]. On the other hand, in the last decade, there has been a renewed interest in recovering and studying local ancient cultivars to preserve the genetic resources of each grape-growing region [31][32][33][34]. This trend could be a valuable strategy to sustain higher genetic diversity, as well as product diversity in the markets.…”
Section: Introductionmentioning
confidence: 99%
“…The existing Vitis vinifera L. varietal diversity is one of the resources to be explored in terms of dealing with climatic change effects and mitigate its consequences [4,[10][11][12][13][14]. Several other reasons are gaining increasing interest from some winegrowers and wineries in recovering minority varieties; a rising interest has been demonstrated in other areas which are linked to grape and wine fields, such as viticulture-related media or consumers; and a highly globalized wine market, as well as the homogenization of wine products have both triggered the study of minority varieties gaining more enthusiasm and importance within recent years [15][16][17][18][19]. Some of these unknown or presently forgotten varieties, as a result of being neglected in past decades due to their lower yields or lower alcoholic degrees, may provide more tolerant genetic resources which are more capable of dealing with the warming climates, thus potentially contributing to increasing the varietal diversity available for the production of distinct and differentiated wines [20].…”
Section: Introductionmentioning
confidence: 99%
“…Among the strategies suggested to cope with the next challenges of agriculture (e.g., climate change, sustainable production and/or competition in a global market) is the exploitation of the intraspecific genetic diversity within crops, including grapevines [4]. Thus, in some grapevine growing regions of the Mediterranean zone, this approach is generating a renewed interest to know the genetic resources available in this species, both in collections and isolated in old vineyards [5][6][7]. Therefore, the prospection, recovery and study of ancient cultivars are becoming very important to preserve the genetic resources of a region.…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, there is an increasing interest to identify and recover forgotten ancient varieties to give a response to the market demanding regional typicity and diversity. These old cultivars show a very narrow regional distribution, but studies focused on their genetic and oenological characterization are showing new sorts of wines that can identify productions from local or small geographical regions, providing them with special recognitions [6,[8][9][10][11]. Moreover, this trend attempts to counterbalance the rapid loss of genetic diversity in vineyards and could be a very positive strategy to maintain higher genetic diversity, as well as product diversity in the markets [12].…”
Section: Introductionmentioning
confidence: 99%